Commercially Available Immunoglobulins Contain Virus Neutralizing Antibodies Against All Major Genotypes of Polyomavirus BK. Issue 4 (3rd March 2015) - Randhawa, P.; Pastrana, D. V.; Zeng, G.; Huang, Y.; Shapiro, R.; Sood, P.; Puttarajappa, C.; Berger, M.; Hariharan, S.; Buck, C. B.
Abstract : Neutralizing antibodies (NAbs) form the basis of immunotherapeutic strategies against many important human viral infections. Accordingly, we studied the prevalence, titer, genotype‐specificity, and mechanism of action of anti‐polyomavirus BK (BKV) NAbs in commercially available human immune globulin (IG) preparations designed for intravenous (IV) use. Pseudovirions (PsV) of genotypes Ia, Ib2, Ic, II, III, and IV were generated by co‐transfecting a reporter plasmid encoding luciferase and expression plasmids containing synthetic codon‐modified VP1, VP2, and VP3 capsid protein genes into 293TT cells. NAbs were measured using luminometry. All IG preparations neutralized all BKV genotypes, with mean EC50 titers as high as 254 899 for genotype Ia and 6, 666 for genotype IV. Neutralizing titers against genotypes II and III were higher than expected, adding to growing evidence that infections with these genotypes are more common than currently appreciated. Batch to batch variation in different lots of IG was within the limits of experimental error. Antibody mediated virus neutralizing was dose dependent, modestly enhanced by complement, genotype‐specific, and achieved without effect on viral aggregation, capsid morphology, elution, or host cell release. IG contains potent NAbs capable of neutralizing all major BKV genotypes. Clinical trials based on sound pharmacokinetic principles are needed to explore prophylactic and therapeutic applications of these anti‐viral effects, until effective small molecule inhibitors of BKV replication can be developed. Abstract : The authors report that commercially available immunoglobulins have been tested for and found to contain virus‐neutralizing antibodies to all major genotypes of polyomavirus BK, with mean EC50 titers as high as 254 899 for genotype I and 666 for genotype IV, no significant batch‐to‐batch variation, and enhanced activity in the presence of complement.